The Future of Education and Artificial Intelligence - Kaur, Gagandeep (Journal of Neonatal Surgery, 2025)
The definition of AI is "automation based on associations." Two key developments in AI occur when computers automate reasoning based on associations in data (or associations inferred from expert knowledge), which elevates computing beyond traditional edtech. First, from gathering data to finding patterns in it; second, from giving students access to educational resources to making judgements about teaching and other procedures related to education automatically. The range of tasks that can be assigned to a computer system increases significantly with the addition of pattern recognition and decision automation. The process of creating an AI system could result in biased decisions being made automatically and biased patterns being identified. As a result, educational systems need to control how AI is used. This paper outlines potential applications of artificial intelligence (AI) in education, identifies impending difficulties, and formulates suggestions to direct future policy development.